2018
DOI: 10.1002/oby.22249
|View full text |Cite
|
Sign up to set email alerts
|

Maternal High‐Fat Diet Effects on Adaptations to Metabolic Challenges in Male and Female Juvenile Nonhuman Primates

Abstract: The current findings indicate that offspring exposed to an mHFD show metabolic adaptations to calorie restriction that are largely similar to those of offspring exposed to a mCTR diet but show delayed adaptation upon exposure to an acute HFDC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…This impairment seemed to be hardly reversed by simple normalized nutritional intake throughout the rest of life, which is different from the results we observed in early life (12 weeks of age) of female HFD offspring. This is consistent with the view that perinatal HFD could alter the ability of offspring to adapt metabolically to a changing nutritional environment, which could underlie the vicious cycle of metabolic syndrome 10 . The alteration of metabolic adaptation may not be obvious in early adult metabolic health, but absolutely influences glucose homeostatic control in the later stage of life.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This impairment seemed to be hardly reversed by simple normalized nutritional intake throughout the rest of life, which is different from the results we observed in early life (12 weeks of age) of female HFD offspring. This is consistent with the view that perinatal HFD could alter the ability of offspring to adapt metabolically to a changing nutritional environment, which could underlie the vicious cycle of metabolic syndrome 10 . The alteration of metabolic adaptation may not be obvious in early adult metabolic health, but absolutely influences glucose homeostatic control in the later stage of life.…”
Section: Discussionsupporting
confidence: 87%
“…This is consistent with the view that perinatal HFD could alter the ability of offspring to adapt metabolically to a changing nutritional environment, which could underlie the vicious cycle of metabolic syndrome. 10 The alteration of metabolic adaptation may not be obvious in early adult metabolic health, but absolutely influences glucose homeostatic control in the later stage of life. Moreover, among the five fat-intake patterns in the present study, perinatal fat restriction during both gestation and lactation, followed by standard food intake in later life, provides the only effective way to restore normal glucose metabolism in aging progeny.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subgroup analysis of rodents versus other species was only possible for selected outcomes (birth weight, body weight, insulin), due to limited numbers of non‐rodent models. While these subgroup analyses showed a similar direction of effect, future studies including non‐rodent models are needed to establish whether non‐human primates for example do in fact display the same responses to maternal obesity as rodents …”
Section: Discussionmentioning
confidence: 86%
“…While these subgroup analyses showed a similar direction of effect, future studies including non-rodent models are needed to establish whether non-human primates for example do in fact display the same responses to maternal obesity as rodents. 94 Second, studies reported poorly on important methodological details (randomization, blinding, and power calculation). This hampered reliable risk of bias assessment and may reduce the reliability of our conclusions.…”
Section: Strengths and Limitationsmentioning
confidence: 99%